Maternal and Cord Blood Saturated Fatty Acid Level and Infant Adiposity - Kusen, Yustiyani; Anwar, Faisal; Dewi, Mira (Jurnal Gizi dan Pangan, 2021)
This study aimed to assess SFAs profiles in the maternal and cord blood, and the relationship of both SFAs levels with infant adiposity. As many as 99 mothers with singleton pregnancy and pre-pregnancy BMI .18.5 agreed to join the research and completed the data collection process. Maternal and cord blood erythrocyte SFAs profile was analyzed using Gas Chromatography-Flame Ionized Detector. Infant birth weight was measured at birth, while infant skinfolds were at 5.7 days postpartum. We used Aris et al. (2013) equation to assess the infant fat mass. The average maternal age was 29.62}5.84 years old, while the pre-pregnancy BMI was 22.87}3.90 kg/m2. Infant birth weight was 3168.83}341.64 g, and fat mass was 9.39}3.52 %. Maternal total SFAs and palmitic acid (C16:0) concentration were higher than cord blood, while lignoceric acid (C24:0) was lower (p<0.05). Increased maternal caproic (C6:0), capric (C10:0), and lauric acids (C12:0) were associated with higher infant adiposity (p<0.05). Total SFAs, palmitic (C16:0), stearic (C18:0), and behenic acids (C22:0) in cord blood were negatively associated with infant adiposity (p<0.05). Elevated lauric (C12:0) and myristic (C14:0) acids in cord blood were associated with greater adiposity. In conclusion, we found a different SFAs profile between maternal blood during the third trimester of pregnancy and cord blood. Increased maternal caproic, capric, and lauric acids as well as cord bloodfs lauric and palmitic acids contribute to greater infant adiposity.